Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

Synthesis and swelling behaviour of hydrophobically modified responsive polymers in dilute aqueous solutions - Iyer, N. P.; Hourdet, Dominique; Badiger, Manohar V.; Chassenieux, Christophe; Perrin, P.; Wadgaonkar, P. (Polymer, 2005)
New series of associating polymers were synthesised in order to investigate opposite behaviours of hydrophobically modified water-soluble polymers and thermoresponsive water-soluble polymers carrying LCST stickers. On the basis of a poly(acrylic acid) backbone, amino-terminated poly(N-isopropylacrylamide), poly(ethylene oxide-co-propylene oxide) and/or dodecyl chains were grafted following a reaction of condensation activated by carbodiimide. Two homologous series of well-defined single grafted and double grafted copolymers were obtained, with double grafted chains containing both C12 and LCST grafts. The dilute solution properties of these copolymers were carefully studied by capillary viscometry. At low salt concentration and below the LCST of the grafts, the swelling properties of macromolecular chains are controlled either by intramolecular associations between hydrophobes, excluded volume effect exerted by hydrophilic grafts or by a balance between these opposite interactions. The deswelling of macromolecular chains, induced by hydrophobic interactions, is amplified at higher ionic strength and more particularly above the transition temperature of the side chains. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: associating polymers; poly(acrylic acid); viscometry

Thermoreversible behavior of associating polymer solutions: thermothinning versus thermothickening - Hourdet, Dominique; Gadgil, Jayant; Podhajecka, K.; Badiger, Manohar V.; Brulet, A.; Wadgaonkar, P. P. (Macromolecules, 2005)
Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST similar to 32 degrees C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scattering patterns were described using a polydisperse sphere model taking into account hard-sphere interactions. This model allow us to draw a realistic picture of physical gels with quantitative information concerning the size of hydrophobic cores, the volume fraction of stickers in the aggregates, the fraction of stickers which take part in the aggregation process, the range of repulsive interactions, and the structural modifications induced by temperature. The description of the network is in good agreement with complementary data obtained from DSC and C-13 NMR. In the present work, a special emphasis has been given to the important relationship existing between the viscoelastic properties of associating polymer solutions and the binding energy of stickers leaving temporarily the micellar junction. Depending on the endothermic or exothermic nature of the disengagement process of the sticker (heat of demicellization), the relaxation time of the network and the viscoelastic properties will either decrease or increase with the temperature. The consequence is that aqueous solutions of PAAgC12 and PAAgPNIPA exhibit opposite rheological properties with the temperature, namely thermothinning and thermothickening. By mixing these two copolymers, we show that intermediate properties can be obtained but in that case a microphase-separated network is obtained as a result of copolymer segregation.

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Synthesis and self-assembling properties of alpha,omega-hydroxy-poly(ethylene oxide) end-capped with 1-isocyanato-3-pentadecylcyclohexane - Kadam, Vijay S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Hourdet, Dominique (Polymer, 2008)
A novel hydrophobic compound, 1-isocyanato-3-pentadecylcyclohexane (PDC) issued from a renewable resource material (Cashew Nut Shell Liquid), is used to end-cap poly(ethylene oxide) (PEO) of different molecular weights. The synthesis, characterization and self-assembling properties of these new associating polymers are reported. In aqueous solution, PDC modified PEOs self-associate into micellar structures which are characterized by neutron scattering. Using a star-polymer model with sticky hard sphere interactions, it is shown that the characteristics of the micelles mainly depend on the size of the PEO chain. In the case of PDC stickers, the aggregation number decreases from 25 to 17 with increasing molecular weight of PEO, from 10 to 20 kg/mol, respectively. The temperature directly impacts the interaction potential between the hydrophilic coronas of PEO which become less repulsive with increasing temperature. Rheological measurements, performed in dilute solution, clearly demonstrate that PEO micelles self-associate into open supramolecular structures. The correlation length of these loose clusters increases with polymer concentration and the hierarchical self-assembly follows the rules of the percolation theory. The sol/gel transition takes place at the overlap concentration of clusters. In semi-dilute solution, the viscoelastic properties of PDC end-capped PEOs are well described by the Maxwell model with a single relaxation mode. The characteristic time of the network follows an Arrhenius temperature dependence with an activation energy of 70 kJ/mol, in very good agreement with the size of PDC stickers. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Hydrophobically end-capped; poly(ethylene oxide); Star micelles

Thermodynamic behavior of hydrophobically modified polyacrylamide containing random distribution of hydrophobes: experimental and theoretical investigations - Hourdet, Dominique; Ducouret, Guylaine; Varghese, Sony; Badiger, Manohar V.; Wadgaonkar, Prakash P. (Polymer, 2013)
Two series of Hydrophobically Modified Polyacrylamides (HMPAMs) were prepared by free radical copolymerization of trimethylsilylacrylamide with 3-pentadecylcyclohexylacrylamide (PDCAM) or dodecylacrylamide (DDAM) followed by removal of trimethylsilyl protecting groups. The solution properties of HMPAMs were studied in dilute aqueous solution by fluorescence spectroscopy, NMR and viscometry. The properties in aqueous solution of HMPAMs clearly displayed the formation of hydrophobic interactions between alkyl stickers. While dodecyl containing HMPAMs mainly showed a progressive collapse of the copolymer coil with the increasing fraction of hydrophobic moieties (weak intra-chain associations), pentadecylcyclohexyl groups containing HMPAMs exhibited a much lower solubility in water due to strong intra- and inter-chain associations. Experimental data were analyzed using the mean field theory developed by Semenov and Rubinstein (SR) for associating polymers. Using a set of realistic parameters, taking into account the solubility of the backbone, the fraction of stickers and the strength of hydrophobic attractions, we show that the SR model offers a quantitative description of the thermodynamic properties of HMPAMs in terms of individual and collective behavior of polymers chains; i.e. swelling and phase separation, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Polyacrylamide; Self-assembling

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Viscoelastic behaviors of hyaluronic derivatives as a function of pH, salt, and temperature - Kadam, Yogesh; Badiger, Manohar V.; Rajamohanan, Pattuparambil R.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Merland, Theo; Hourdet, Dominique (Journal of Polymer Science, 2026)
Hyaluronic acid and its derivatives are essential polysaccharides widely used in the bio-medical field for their applications in tissue engineering and controlled drug delivery. By revisiting the wide variety of rheological behavior of aqueous hyaluronan solutions as a function of pH, we develop in this work a comparative study between solutions of native hyaluronan (HA) and its derivative (HA-PEPO) obtained by grafting onto thermoresponsive side-chains of poly(ethylene oxide-co-propylene oxide) characterized by a phase transition around body temperature. Based on a large dataset obtained at a fixed polymer concentration, by changing either the chemical composition of the chain and/or the environmental conditions (pH, temperature, added salt), we show that the viscoelastic properties of hyaluronan solutions can be controlled over more than three decades of amplitude with the possibility to get either liquid or gel states, regardless of temperature, as well as sol/gel transitions induced by cooling or heating by the interplay between hydrogen bonds, hydrophobic interactions, and cation binding induced by potassium salts.
Keywords: hyaluronan; Hydrogel; pH-induced gelation; salt-induced gelation; thermoresponsive polymers; tissue engineering